Review of: Polinsky, Maria (ed.). 2021. Oxford handbook of the languages of the Caucasus - Wier Thomas R. (Linguistic Typology)
This paper presents a general review of the Oxford Handbook of the Languages of the Caucasus. It summarizes over four dozen different typological rarities found in Caucasian languages, and examines what explanations have been given for their presence, and what roles phylogeny, contact and human geography play in their appearance in these languages.